Analisis Perbedaan Kebersihan Gigi pada Lanjut Usia Berdasarkan Status Frailty - Alifia Bahriyah Putri (Fakultas Kedokteran Gigi, 2026)
Background: Indonesia is experiencing an aging population phenomenon characterized by an increase in the number of older adults. As they age, older adults experience a decline in physical function that can increase the risk of frailty. Frailty is a condition of vulnerability due to a decline in physical reserves and function. Frailty can cause limitations in daily activities, including maintaining dental hygiene. However, research examining dental hygiene based on frailty status among older adults in Indonesia remains limited. Objective: This study aimed to analyze the differences in dental hygiene among older adults based on frailty status. Methods: This study was conducted in Jelbuk and Balung Subdistricts, Jember Regency and involved 100 participants aged ≥ 60 years. Frailty status was assessed using the Frailty Index for Elders (FIFE) questionnaire. Dental hygiene was measured using the O'Leary Plaque Index by applying a dye agent to four tooth surfaces. Data were analyzed using the Kruskal-Wallis test and Spearman's rank correlation to determine the differences in dental hygiene among older adults based on frailty status and correlations between variables. Results: The Kruskal-Wallis test shows significant differences in dental hygiene across frailty groups (H = 42.39, p < 0.01): Non-Frailty (25.67), Risk Frailty (57.99), and Frailty (70.32). Spearman's rank correlation indicates a significant and strong association between frailty status and dental hygiene in older adults (r = 0.62, p < 0.01). Conclusion: Older adults with non-frailty status have better dental hygiene compared to those with risk frailty and frailty.
Finalisasi 22 Juli 2026_Yudi
Keywords: frailty; older adults; dental hygiene; plaque